The Influence of Financial Literacy and the Utilization of the Financial Information Recording Application System (SIAPIK) Mediated by Financial Inclusion on Credit Access - Kholifah, Nur; Rahman, Sulaeman; Sutisna, Sutisna (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to examine the effect of financial literacy and the use of the SIAPIK application mediated by financial inclusion on access to credit for MSMEs. This study uses a quantitative research method with a descriptive approach to analyze the results of the distributed questionnaires. The population in this study were MSMEs that collaborated with Bank Indonesia Cirebon and used the SIAPIK application in their financial records. To determine the number of samples, the Slovin formula was used, so that the total number of samples was 60 samples. The data analysis used was the SEM-PLS method with the Smart PLS 4 application. The results of this study found that financial literacy has a positive and significant effect on access to credit for MSMEs. The use of the SIAPIK application has a positive but not significant effect on access to credit, indicating that the role of this application is still limited in influencing access to financing. Financial inclusion also has a positive and significant effect on access to credit, indicating that connectivity with formal financial services facilitates access to financing. Financial literacy has been shown to have a positive and significant effect on financial inclusion. However, financial inclusion is unable to mediate the relationship between financial literacy and the use of the SIAPIK application on access to credit.